Implementation of Merdeka Belajar in Indonesian Language Learning in Senior High Schools - Muhsyanur, Muhsyanur (Jurnal Ilmiah Insan Mulia, 2024)
This qualitative case study explores the implementation of the "Merdeka Belajar" (Freedom to Learn) approach in Indonesian language learning at the senior high school level. The study investigates the perceptions and practices of Indonesian language teachers, the alignment between Merdeka Belajar principles and classroom instruction, and the challenges and opportunities associated with this innovative curriculum framework. Data was collected through semi-structured interviews, classroom observations, and the analysis of curricular materials. The findings reveal a varied landscape of Merdeka Belajar implementation, with some teachers enthusiastically embracing the approach and others struggling to adapt. Key factors influencing the process include teacher beliefs, administrative support, and the broader educational ecosystem. The study highlights the potential of Merdeka Belajar to transform Indonesian language education by fostering student-centered, personalized, and technology-enhanced learning experiences. The insights gained can inform policymakers, school leaders, and educators in their efforts to effectively integrate the Merdeka Belajar approach and deliver a more empowering and relevant language curriculum.